Field‐Effect Transistors: Threshold Voltage Control of Multilayered MoS2 Field‐Effect Transistors via Octadecyltrichlorosilane and their Applications to Active Matrixed Quantum Dot Displays Driven by Enhancement‐Mode Logic Gates (Small 7/2019). Issue 7 (15th February 2019) - Roh, Jeongkyun; Ryu, Jae Hyeon; Baek, Geun Woo; Jung, Heeyoung; Seo, Seung Gi; An, Kunsik; Jeong, Byeong Guk; Lee, Doh C.; Hong, Byung Hee; Bae, Wan Ki; Lee, Jong‐Ho; Lee, Changhee; et al.
Abstract : In article number1803852, Changhee Lee, Sung Hun Jin, and co‐workers develop an adjustment scheme for threshold voltage of multi‐layered MoS2 field effect transistors via octadecyltrichlorosilane treatment on the back channel of multi‐layered MoS2 . More impressively, enhancement‐mode MoS2 logic gates and active matrixed quantum dot pixels are successfully demonstrated, which can be potentially utilized for next‐generation device opportunities.